floor
Patent Information
- Application Number
- KR1020227045496
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-25
- Filing Date
- 2021-06-24
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-06-24
Smart Images

Figure 112022139199011-PCT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for depositing a ceramic film on a ceramic or metal surface, in particular for depositing ytterbium-doped zirconia with a sub-micron thickness. The present invention is particularly useful for manufacturing high-temperature and medium-temperature operating electrochemical cells, including solid oxide cells (SOC), in particular metal-supported medium-temperature SOCs operating in the range of 450°C to 650°C. Background Technology
[0002] Fuel cells, fuel cell stack assemblies, fuel cell stack system assemblies, etc. are well known in the prior art, and relevant teachings include those of WO 02 / 35628, WO 03 / 075382, WO 2004 / 089848, WO 2005 / 078843, WO 2006 / 079800, WO 2006 / 106334, WO 2007 / 085863, WO 2007 / 110587, WO 2008 / 001119, WO 2008 / 003976, WO 2008 / 015461, WO 2008 / 053213, WO 2008 / 104760, WO 2008 / 132493, and WO 2009 / 090419, all of which are incorporated herein by reference in their entirety It is integrated. The fuel cell can be used in reverse mode as an electrolytic cell. Therefore, the designations cathode and anode (used for brevity and due to broader fuel cell applications) below should effectively be interpreted as designations for the air (or oxidizer) electrode and the fuel electrode, respectively, and these terms apply to the cell regardless of whether the cell operates in fuel cell or electrolytic cell mode.
[0003] Over the years, efforts have been made to lower the operating temperature of the SOC from the conventional 800°C to 1000°C to 600°C or lower. It has been recognized that achieving this requires the use of a different set of materials than those traditionally used in the SOC. In particular, when operating at 450°C to 650°C, this entails the use of cathode materials with increased catalytic activity and electrolyte materials with higher oxygen ion conductivity than conventional yttrium-stabilized zirconia (YSZ).
[0004] High-performance cathode materials are typically perovskite oxides based on cobalt oxides, such as LSCF (lanthanum strontium cobalt ferrite), LSC (lanthanum strontium cobaltite), and SSC (samarium strontium cobaltite). Electrolyte materials with higher conductivity are typically (i) rare-earth-doped ceria, such as SDC (samarium-doped ceria) and GDC (gadolinium-doped ceria), or (ii) materials based on lanthanum gallate, such as LSGM (lanthanum-strontium-magnesium gallate).
[0005] The conductivity of zirconia can also be significantly improved by doping with Scandia rather than yttria, but Scandia is a more expensive material.
[0006] Unfortunately, materials that exhibit higher performance at lower temperatures are frequently less stable than conventional high-temperature materials. Specific problems that frequently occur are as follows:
[0007] High-performance cathode materials react with zirconia to form strontium or lanthanum zirconate, which are very poor ion conductors and lead to performance degradation.
[0008] LSGM reacts with nickel oxide, which is typically found in the anode.
[0009] Doped ceria can be partially reduced when exposed to a fuel atmosphere, resulting in mixed ion / electron conductivity. This, in turn, causes the cell to develop an internal short circuit, thereby reducing operating efficiency.
[0010] ㆍ Doped ceria and zirconia may react when processed at temperatures exceeding 1200°C, producing a poorly conductive mixed phase.
[0011] To mitigate these undesirable material interactions, it is frequently desirable to have a composite electrolyte comprising a main layer and one or more intermediate layers. The main layer performs the primary function of conducting oxygen ions between the cathode and anode and providing a hermetic barrier to physically separate the reactants. The intermediate layer(s) are thin film(s) of another electrolyte material that separate the main electrolyte layer from one or both electrodes to prevent harmful interactions. Typical uses of the intermediate layer include the following:
[0012] An intermediate layer of doped ceria deposited between the zirconia main electrolyte layer and the cobaltite cathode to avoid the formation of zirconate and improve the catalytic activity of the cathode.
[0013] An intermediate layer of doped ceria deposited between the LSGM main electrolyte and the anode to avoid reaction with nickel oxide found at the anode.
[0014] ㆍ Doped zirconia intermediate layer between CGO electrolyte and electrode to prevent electron conductivity.
[0015] It is known that the fabrication of thin (less than 1 μm) and uniform continuous impermeable films is not a simple process for cost-effective fuel cell manufacturing. Material quality, reproducibility, and process costs mean that traditional powder, sintering, and plasma or vacuum spray deposition routes are not attractive for mass production. Furthermore, in the case of metal-supported SOCs, for example, where the substrate is a ferrite stainless steel foil coated with an active electrochemical layer (e.g., a perforated foil substrate), the substrate material places limitations on acceptable manufacturing processes.
[0016] WO 2009 / 090419 discloses a process for manufacturing thin films of scandium-stabilized zirconia (ScSZ) for use in SOCs. However, while the electronic and structural properties achieved by this system are excellent, it is desirable to achieve at least comparable results using more readily available and less expensive materials.
[0017] Literature [Korkmaz, et al.; " Synthesis and Characterizations of YbSZ Film Electrolytes [7th INTERNATIONAL EGE ENERGY SYMPOSIUM & EXHIBITION; 18 June 2014] discloses a sol-gel Pechini method in which an ytterbium-doped zirconia film is formed and sintered at a high temperature (1400°C).
[0018] Literature [Benitez-Rico, et al.; " Understanding the High Ionic Conductivity in Nanostructured Ytterbium Stabilized Zirconia Thin Films [JOURNAL OF NANOMATERIALS; Volume 2015; Article ID 692648; pages 1 to 7] discloses a pyrolysis technique for manufacturing a thin film of ytterbium-doped zirconia for use as an electrolyte in a solid oxide fuel cell. The problem to be solved
[0019] The present invention is intended to overcome or at least improve one or more of the above problems. means of solving the problem
[0020] In a first aspect of the present invention, a method for manufacturing a layer for a solid oxide cell is provided, wherein the layer comprises crystalline ytterbium-doped zirconia, and the method comprises the following steps: (i) depositing a solution comprising a precursor metal salt of ytterbium-doped zirconia onto a surface of a substrate, wherein the surface is a metal or ceramic surface; (ii) drying the solution to form a layer of the precursor metal salt on the surface; (iii) heating the layer of the precursor metal salt to form ytterbium-doped zirconia; (iv) optionally repeating steps (i) through (iii); and (v) calcining the layer to form the crystalline ytterbium-doped zirconia.
[0021] The inventors have discovered that doping zirconia with ytterbium produces a layer having performance comparable to that described in WO 2009 / 090419 without relying on more expensive dopant elements, such as scandium. Furthermore, surprisingly, it was discovered that the presence of ytterbium in the deposition solution allows a higher concentration of zirconium to be dissolved in the deposition solution. This, in turn, means that the deposition rate of the precursor salt on the substrate can be increased because the same volume of solution will deliver more zirconium salt to the substrate. This is particularly useful for mass production, as it leads to significant cost savings by reducing the number of deposition steps required to achieve ytterbium-doped zirconia of a specific thickness. Additionally, when ytterbium is used as a dopant, the uniformity of the shape achieved from the deposited film is improved. This means that fewer deposition cycles and fewer films are required to achieve a layer with the same flatness and uniformity of shape (for example, compared to such layers manufactured using 10Sc1YSZ in WO2009 / 090419). This, in turn, improves the speed and cost of manufacturing.
[0022] Unbound by theory, these properties are Sc 3+ Much heavier and more severely polarized Yb 3+ It is hypothesized that this may be due to the lower pH generated by the ions. Lanthanide series ions, particularly heavier ions, are known to interact particularly strongly with the solvent due to electrostatic effects from highly positively charged nuclei poorly shielded by 4f electrons.
[0023] Ytterbium-doped zirconia may also be referred to as ytterbium-stabilized zirconia (YbSZ), which is familiar to those skilled in the art. Crystalline ytterbium-doped zirconia will typically have a cubic crystal structure.
[0024] The substrate may include a dense solid oxide electrolyte for a solid oxide cell, and a layer of crystalline ytterbium-doped zirconia is formed on the substrate.
[0025] The term "solid oxide cell" is intended to include both solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs). Typically, the present invention is implemented in relation to SOFCs.
[0026] Typically, a "layer" of ytterbium-doped zirconia refers to an entire functional sheet of the material. For example, the anode, electrolyte, and cathode are each considered as individual layers of the SOC, but each of these layers may have a structure comprising multiple deposited films of the material. Typically, the layer is an intermediate layer. The intermediate layer is typically applied to the electrolyte and is most typically located between the electrolyte and the cathode (or air electrode). The location of the intermediate layer does not necessarily have to be immediately adjacent to the cathode, and in some embodiments, a barrier layer is located between the intermediate layer and the cathode. In some embodiments, this barrier may be a thin film of the electrolyte. The layer may comprise crystalline ytterbium-doped zirconia having a single-phase cubic crystal structure.
[0027] As used herein, the term "film" refers to a single plane of material resulting from a single deposition step. Multiple films may be deposited through the repetition of steps (i) through (iii) and the repetition of steps (i) through (v) to create a laminar (or laminated) structure, which are taken together to form a "layer" (see above).
[0028] The ytterbium-doped zirconia layer formed in the heating step (iii) of the present invention will typically be an "amorphous" layer. This layer does not need to be completely amorphous. The purpose of the heating step (iii) is, in particular, to convert (or decompose) the precursor salt deposited on the substrate surface into a metal oxide of ytterbium and zirconia, namely ytterbium-doped zirconia. Typically, the heating step is configured so that substantially all of the precursor salt is converted. Thus, this may be the case where a portion of the ytterbium-doped zirconia becomes crystalline during step (iii) before the firing step (v). In step (v), substantially all of the amorphous ytterbium-doped zirconia is converted into crystalline ytterbium-doped zirconia.
[0029] "Solution" refers to a true solution composed of at least one substance (solute) among at least one other substance (solvent), that is, excluding the presence of solid particles, and thus excluding liquid colloidal dispersions, colloidal solutions, and mechanical suspensions.
[0030] To avoid any doubt, the designation "room temperature" (or "RT") herein is intended to refer to values in the range of 10°C to 40°C, more typically 20°C to 30°C.
[0031] Experiments performed by the inventors indicated that the presence of solids in the film of step (i) creates stress points, which lead to cracking and consequently loss of layer integrity. Accordingly, the inventors found that it is desirable to have a thin-layer deposition process that dries and anneales in a homogeneous manner. Depositing a homogeneous layer enables homogeneous drying and annealing with a low risk of cracking. Layers prepared from sol-gel mixtures or suspensions containing solid particles tend to dry in a non-uniform manner and sinter in a heterogeneous manner, and the suspension region dries faster than the region surrounding the particles or gel, creating mechanical drying and annealing stresses, which can lead to cracking. Therefore, to produce a layer of sufficient thickness, it is often necessary to deposit multiple films.
[0032] Typically, the temperature of the firing step (v) is in the range of 500°C to 1100°C, more typically 700°C to 1000°C, and more typically 1000°C or lower. The layer formed by the process of the present invention is typically intended for use in a metal-supported SOC, where the metal support is typically made of steel. At process temperatures above 1100°C, more rapid oxidation of this steel occurs, and migration of volatile metal species may also occur. This is particularly true for stainless steels such as ferritic stainless steel, where chromium migrates to other parts of the cell (e.g., cathode, electrolyte, or anode). This is known to result in a loss of cell performance.
[0033] The present invention is particularly applicable to metal-supported intermediate temperature (e.g., typically operating at less than 650°C) electrochemical cells, such as the fuel cell designs disclosed in GB2368450 and GB2434691. More particularly, the present invention is useful for the manufacture of an intermediate layer comprising crystalline ytterbium-doped zirconia deposited together with a doped ceria electrolyte of a fuel cell. The crystalline ytterbium-doped zirconia electronically insulates the fuel cell electrodes from one another, thereby preventing internal short circuits.
[0034] Typically, the surface of the substrate on which the ytterbium-doped zirconia precursor salt is deposited is generally flat or continuously smooth. Often, the surface of the substrate is generally impermeable, i.e., non-porous, and impermeable to liquids, particularly solutions of the precursor metal salt. Typically, the substrate can withstand rapid thermal cycling.
[0035] Accordingly, the method of the present invention is particularly suitable for the production of an intermediate layer of crystalline ytterbium-doped zirconia as part of a SOC, more typically a low-temperature or medium-temperature SOC. In particular, the method of the present invention is highly suitable for the production of a crystalline ytterbium-doped zirconia layer as part of a metal-supported SOC, more typically a low-temperature or medium-temperature metal-supported SOC, wherein the inherent rigidity of the metal support (often a foil made of stainless steel such as ferritic stainless steel, more typically a foil having a perforated area surrounded by a non-perforated area) allows for rapid thermal cycling while placing a limit on the maximum process temperature.
[0036] Accordingly, the substrate is typically an electrolyte layer, more typically an electrolyte layer made of a mixed ionic electronic conductive electrolyte material, and more typically a CGO electrolyte layer.
[0037] Often, crystalline ytterbium-doped zirconia layers are dense. Typically, crystalline ytterbium-doped zirconia layers are at least 90% dense (i.e., at least 90% of their theoretical density). In some cases, this is at least 91%, 92%, or 93% dense. Most commonly, it is at least 93% dense. As a person skilled in the art knows, achieving 100% theoretical density is difficult. Thus, crystalline ytterbium-doped zirconia typically ranges in density from 90% to 99.5%, more typically from 91% to 99%, and more typically still from 92% to 98%. Crystalline ytterbium-doped zirconia layers are typically gas impermeable. This is particularly relevant to the use of the present invention in the manufacture of fuel cell electrolytes in which it is desirable for the intermediate layer to be ion-permeable, electrically insulating, and gas-impermeable to prevent internal short circuits.
[0038] When a solution of a salt precursor is deposited on a surface, it is desirable for it to spread and dry as a continuous and uniform film. Typically, a soluble salt precursor solution of ytterbium-doped zirconia is deposited on a surface by a method selected from the group consisting of spraying, immersion, atomization (e.g., inkjet printing), and spin coating. Examples of spraying techniques are air- and gas-assisted spraying.
[0039] Typically, soluble salt precursors are dissolved in solvents with low surface tension. Typical solvents include methanol, ethanol, propanol, methoxypropanol (also known as MEP, 1-methoxy-2-propanol, PGME, 1-methoxypropan-2-ol, and propylene glycol methyl ether), ethyl acetate, acetone, butyl carbitol, or any mixture thereof. Among these, ethanol, methanol, ethyl acetate, methoxypropanol, and mixtures thereof are typically used. In some cases, a mixture of ethanol and methoxypropanol, or ethyl acetate and methoxypropanol, will be used. Typically, ethanol or ethyl acetate is used as the primary solvent. In some embodiments, ethyl acetate is used as the solvent. Typically, the ratio of ethanol (or ethyl acetate) to methoxypropanol will be in the range of 95%:5% to 50%:50%, more typically 95%:5% to 85%:15%, and most typically about 90%:10%. When selecting a solvent for a soluble salt precursor, factors to be considered include the solubility of the precursor in the solvent, the drying rate, and how easily the soluble salt precursor layer on the surface will become uniform due to surface tension effects. A suitable solvent will be readily apparent to a person skilled in the art.
[0040] Typically, the solution has a pH in the range of 2 to 6, more typically 2 to 5, more typically 2 to 4, and most typically 3 to 4. In some cases, the pH is in the range of 2 to 3. Typically, the solution further comprises an acid, typically a weak acid. The acid may be selected from acetic acid, citric acid, nitric acid, or a combination thereof. Surprisingly, the applicant has discovered that the optional use of the acid improves the stability of the solution, thereby improving its shelf life and / or allowing for the use of a more concentrated solution, the latter allowing for the deposition of more material in a single pass and, consequently, a reduction in the number of deposition passes required. The weak acid, e.g., acetic acid, is typically used in an amount of up to 3 volume%, more preferably up to 2% or 1% based on the total volume of the solution, and an amount of 0.25% to 0.9% is ideal. For example, a higher acetic acid concentration (e.g., 2 volume% to 3 volume%) acts but may adversely affect the drying characteristics of the layer.
[0041] As described above, the soluble salt precursor needs to decompose upon heating to leave, as much as possible, only (amorphous) ytterbium-doped zirconia. Suitable salts include, but are not limited to, nitrates and metal-organic salts. Metal-organic salts are often used because they typically form excellent films. Among these salts, acetylacetonates are typically used. A binder may be included in the solution if desired.
[0042] As may be noted, the precursor salts of ytterbium-doped zirconia films do not necessarily have to be formed solely from ytterbium and zirconium salts. Additional soluble salt precursors may be added to form mixed crystalline ytterbium-doped zirconia. Typically, crystalline ytterbium-doped zirconia has the following chemical formula:
[0043] ([Yb x M 1-x ]2O3) z (ZrO2) 1-z
[0044] In the above formula, M is a metal dopant ion; z is in the range of 0.03 to 0.13; and x is in the range of 0.05 to 1. Typically, x is in the range of 0.5 to 1.
[0045] M can be a trivalent metal ion. M can be selected from any one or more of the group of lanthanide elements, excluding ytterbium and promethium. Typically, the lanthanide elements are selected from La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Lu. Often, the lanthanide elements are Ce, Sm, Er, and Lu. Alternatively, M can be a transition metal selected from Sc, Y, and Al, most typically from Sc or Y.
[0046] Often, z is in the range of 0.03 to 0.13, more typically 0.06 to 0.12, and even more typically 0.07 to 0.10. When x=1 so that there is no dopant M, YbSZ is stabilized in a cubic form in the range of 6 mol% to 12 mol% Yb2O3 (i.e., mol% for oxide), and thus z is in the range of 0.06 to 0.12. This assists the crystalline ytterbium-doped zirconia in adopting the desired (single-phase) cubic crystal structure. When z is in the range of 0.07 to 0.10, much better conductivity is exhibited, and maximum conductivity occurs when z is approximately 0.08. Thus, 8 mol% ytterbium-stabilized zirconia (8YbSZ, (ZrO2) 0.92 (Yb2O3) 0.08 ) is optimal. However, z can be as low as 0.03, and for 3 mol% to 5 mol% Yb2O3, crystalline ytterbium-doped zirconia adopts a tetragonal / cubic phase, which has lower conductivity but is mechanically stronger.
[0047] Typically, the deposition technique used in step (i) is spraying or atomizing. In particular, the spraying may be ink spraying. The atomizing may be by atomized spraying, more typically by air atomized spraying. Spraying often occurs using an atomizer or an ultrasonic atomizer. Typically, the deposition step (i) occurs in a single spray or spraying pass. Typically, the deposition step (i) is performed at a temperature ranging from 10°C to 100°C, more typically from 15°C to 50°C, and more typically at room temperature. Typically, the temperature is the surface temperature of the substrate, that is, the deposition step (i) is performed using a surface of a substrate (or a metal oxide film, where appropriate) having a temperature ranging from 10°C to 100°C, more typically from 15°C to 50°C, and more typically at room temperature.
[0048] Deposition can be performed using a jetting head. Ideally, the liquid is deposited as individual droplets of a fixed volume, with the deposition frequency and speed of the XY stage adjusted so that the liquid droplets cover the entire surface of the portion without overlapping. Subsequently, the droplets are spread and combined on the portion after deposition to form a uniform liquid film, and upon drying, the total volume is adjusted to achieve a predetermined film thickness. Typically, it is not necessary to heat the substrate, and a substrate temperature in the range of 15°C to 50°C is sufficient to achieve a cohesive, uniform film.
[0049] Typically, a film of a soluble salt precursor deposited on a substrate surface is allowed to become uniformly thick prior to the drying step (ii). Accordingly, the method may further include a step prior to step (ii) that allows the solution deposited on the surface to be left for a period of at least 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60 seconds. The solution is typically left to be left for 5 minutes or less. This post-deposition residence time typically occurs in air under standard atmospheric conditions at room temperature, more typically at a temperature in the range of 15°C to 50°C. During this residence time, the film typically begins to dry.
[0050] The drying step is important because incorrect drying conditions can result in uneven thickness of the soluble salt precursor film (after the drying step) and, consequently, an uneven layer of ytterbium-doped zirconia. The more uneven the soluble salt precursor film is after drying, the greater the likelihood of cracking, especially where it is thickest.
[0051] The inventors have discovered that controlling the temperature during the deposition step (i), particularly during the repeated deposition step, can improve the quality of the layer. Deposition of a film of a solution of a soluble ytterbium-doped zirconia salt precursor immediately after the completion of the heating step (iii) while the surface temperature of the substrate (or metal oxide film) is above 100°C results in rapid drying of the solution and the formation of a soluble salt precursor layer with uneven thickness. This, in turn, leads to an increased tendency for cracking and mechanical defects in the resulting ytterbium-doped zirconia layer, thereby reducing the product life.
[0052] Typically, at least 90% of the solvent in the solution of the soluble salt precursor deposited, more typically at least 95% of the solvent, and most typically >95% of the solvent are removed by the end of the drying step (ii). Typical conditions for the drying step (ii) are a temperature in the range of 15°C to 50°C, more typically room temperature.
[0053] Under specific conditions (e.g., when a specific type of solvent is used or when used under specific atmospheric conditions), additional heating may be required during the drying step (ii) to achieve >90% solvent evaporation. For example, during the drying step, the solution of the soluble salt precursor may be heated to about 100°C for a period sufficient to achieve >90% solvent evaporation. The drying step removes sufficient solvent (typically >90%) to produce a stable, cohesive, and uniform film for further processing.
[0054] The step of heating a soluble salt precursor on a substrate to decompose it and form a ytterbium-doped zirconia layer that is mostly amorphous typically includes heating the soluble salt precursor to a temperature in the range of 200°C to 600°C, typically above 300°C, more typically up to about 550°C. The degree of crystallinity produced in the heating step (iii) is typically 50% or less, more typically 40% or less, more typically 30% or less, most typically 20% or less.
[0055] The step of heating the soluble salt precursor on the surface to a range of 200°C to 600°C can cause crystallization to begin. Thus, the ytterbium-doped zirconia layer can therefore be considered semicrystalline. However, at the end of the heating step (iii), crystallization is incomplete, and a sintering step (v) is still required to achieve more complete crystallization.
[0056] Typically, heating is achieved by using a rapid heating source, such as an infrared heat source. This allows heating to be achieved uniformly and conveniently in less than 5 minutes, typically 4 minutes, 3 minutes, 2 minutes, or less than 1 minute. More typically, the heating step (iii) occurs for less than 60 seconds, often 5 seconds or more. Such rapid heating allows for rapid throughput of the cell during manufacturing processing.
[0057] The maximum film thickness achievable per cycle of deposition, drying, and heating depends on the prevention of cracking during the drying step (ii) or the heating step (iii).
[0058] Typically, each film of amorphous ytterbium-doped zirconia has a thickness in the range of 10 nm to 999 nm, more typically 25 nm to 250 nm, more typically 50 nm to 200 nm, more typically 75 nm to 150 nm, and more typically 100 nm to 150 nm. Typically, step (iv) is performed at least once, but often 10 times or less, more typically 8 times or less, more typically still 6 times or less, much more typically 4 times or less, and more typically still 3 times or less. Most typically, step (iv) is performed 2 times or less, that is, to produce a layer consisting of 2 or 3 films, most typically 3 films.
[0059] Steps (i) through (iii) may be repeated to define a plurality of films of an amorphous ytterbium-doped zirconia precursor on the surface of the substrate. Typically, following the heating step (iii) and before the repetition of the deposition step (i), the substrate and the amorphous ytterbium-doped zirconia film are cooled to a temperature below the decomposition temperature used in the heating step (iii), more typically <100°C, more typically still <50°C, and typically to room temperature. In a mass manufacturing plant, rapid cooling can be achieved by placing the coated substrate (e.g., metal foil) on a cold surface, such as a water-cooled metal plate (where rapid heat transfer from the substrate with a relatively low thermal mass to the metal plate's relatively large and colder thermal mass can occur). Other cooling mechanisms will be obvious to those skilled in the art. With a simple process, it is possible for the cell to be cooled in air prior to subsequent processing steps.
[0060] Different soluble salt precursors may be used in each repetition of steps (i) to (iii), thereby producing a plurality of films to form a layered structure within an ytterbium-doped zirconia layer, wherein at least one of the films comprises ytterbium-doped zirconia. Accordingly, for example, a soluble salt precursor selected from the group consisting of zirconium acetylacetonate and ytterbium nitrate pentahydrate may be used in steps (i) to (iii), and in repetitions of steps (i) to (iii), the soluble salt precursor may be selected from the group consisting of cerium acetylacetonate and gadolinium nitrate. Accordingly, the crystalline ytterbium-doped zirconia layer produced in step (v) may be a layer comprising a first crystalline ceramic ytterbium-doped zirconia film and a second crystalline ceramic CGO film.
[0061] Both the drying step (ii) and the heating step (iii) result in significant shrinkage of the soluble salt precursor layer. If the layer is sufficiently thin, the shrinkage stress accumulated as a result of drying and / or heating does not lead to cracking or mechanical failure, and a dense and defect-free ytterbium-doped zirconia layer is formed. However, if the layer is too thick, the shrinkage stress can lead to cracking or even delamination and thus failure of the resulting layer.
[0062] Additional shrinkage occurs during crystallization, i.e., during the firing step (v), and thus the maximum thickness of the crystalline ytterbium-doped zirconia in the present invention is defined in part by the fact that it can be achieved without cracking during crystallization. The thickness of the ytterbium-doped zirconia layer is also determined by the number of successive deposition and heating steps performed prior to crystallization, and the thickness of each of these films is limited as described above.
[0063] The actual maximum allowable thickness of the ytterbium-doped zirconia layer before crystallization will be determined by factors such as the material being deposited, the degree of shrinkage of the material upon crystallization, the level of residual material (e.g., carbon) left from the heating process, and the flatness of the deposited layer.
[0064] Typically, the resulting crystalline ytterbium-doped zirconia layer formed after the completion of one set of steps (i) to (v), i.e., a single firing step (v), followed by optionally multiple deposition passes (i) to (iii), has a thickness in the range of 100 nm to 999 nm, more typically 200 nm to 800 nm, more typically 250 nm to 700 nm, and most typically 400 nm to 600 nm.
[0065] Typically, after the firing step (v), the crystalline ytterbium-doped zirconia layer is substantially and completely crystallized into a layer of ytterbium-doped zirconia crystalline ceramic (bonded to the substrate), and more typically, completely crystallized. Typically, the layer of ytterbium-doped zirconia crystalline ceramic is impermeable. Typically, the layer of ytterbium-doped zirconia crystalline ceramic is generally continuous, that is, it is not cracked, or is not porous, or is not perforated, or is not permeable, or otherwise is not mechanically fractured.
[0066] If it is desirable to provide a thicker layer of ytterbium-doped zirconia crystalline ceramic, steps (i) through (v) may be repeated (i.e., performing another set of steps (i) through (v) ultimately leading to an additional sintering step), wherein the surface used for deposition is a previously prepared (by the first set) crystalline ytterbium-doped zirconia layer. However, typically, it is desirable to avoid an additional sintering step to prevent unwanted metal ion species from migrating from the substrate (typically stainless steel) to the fuel cell electrolyte and / or electrode, and to prevent the growth of an unwanted oxide layer on the substrate. Often, when steps (i) through (v) are repeated fewer times, they are repeated three times or less, more typically two times or less, and most typically once.
[0067] Accordingly, the above method may further include the step of repeating steps (i) to (v) (wherein step (iv) is optional) at least once, and the surface is a layer of ytterbium-doped zirconia crystalline ceramic previously prepared in step (v). Thus, it is possible to further increase the total layer thickness by depositing an additional film on top of the crystallized ytterbium-doped zirconia layer after intermediate crystallization.
[0068] When using step (v), each iteration of steps (i) through (v) does not need to be performed using the same conditions as the previous iteration. Thus, different solutions of different soluble salt precursors of the same or different metal oxide crystalline ceramics may be used. In practice, subsequent layers of the material also do not need to include crystalline ytterbium-doped zirconia. Step (iii) may or may not be included in the iteration, and if included, steps (i) and (ii) may be repeated a different number of times.
[0069] As such, this is typically the case where, after steps (i) through (v) are completed including any repetition of step (v), the crystalline ytterbium-doped zirconia layer has a total thickness in the range of 100 nm to 2.0 μm, more typically in the range of 400 nm to 1.5 μm, more typically in the range of 800 nm to 1.4 μm, and most typically in the range of 0.9 μm to 1.2 μm.
[0070] Accordingly, it is also possible to produce a series of films (at least one of which comprises ytterbium-doped zirconia crystalline ceramic) and, by repeating steps (i) through (v) a desired number of times (the product thereof may be processed as a layer of a single material), to produce a plurality of distinct films of metal oxide crystalline ceramics on top of each other on a surface. Each film of metal oxide crystalline ceramic is identical to or different from a previously produced layer of metal oxide crystalline ceramic, provided that at least one of the layers comprises crystalline ytterbium-doped zirconia.
[0071] For example (and as described above), within an SOC anode-electrolyte-cathode layer structure, it may be highly desirable to provide an electrically insulating ion-conducting layer within a mixed ionic electronic-conducting electrolyte layer. Accordingly, an intermediate layer in the form of a layer of gas-impermeable, ion-permeable, and electrically insulating ytterbium-doped zirconia crystalline ceramic can be deposited on top of a CGO main layer (a layer of metal oxide crystalline ceramic). Typically, a relatively thin additional CGO layer is deposited on top of the intermediate layer, i.e., between the intermediate layer and the cathode.
[0072] Accordingly, the method of the present invention may include step (v) as described above, wherein: in the first set of steps (i) to (v), the soluble salt precursor is selected from at least one of the group consisting of zirconium acetylacetonate and ytterbium nitrate pentahydrate; and in the second set of steps (i) to (v), the soluble salt precursor is selected from at least one of the group consisting of cerium acetylacetonate and gadolinium nitrate.
[0073] The method of the present invention can be used to manufacture a solid oxide cell having an anode-electrolyte-cathode layer structure, wherein one or more intermediate layers are provided. Typically, at least one intermediate layer is positioned adjacent to the electrolyte to insulate the electrolyte from the electrodes. In some embodiments, the intermediate layer is positioned between the electrolyte and the two electrodes, but most typically, a single intermediate layer is positioned between the electrolyte and the cathode. As described above, the intermediate layer does not necessarily have to be positioned immediately adjacent to the cathode. A barrier layer may be provided to prevent direct contact between the intermediate layer and the cathode, which is typically made of the same material as the electrolyte.
[0074] In another embodiment, the thickness of the ytterbium-doped zirconia crystalline ceramic layer can be graded across the surface. Such graded thickness of the ytterbium-doped zirconia crystalline ceramic layer can be achieved, for example, by using spray masks of different sizes in a successive deposition step (i.e., repeating steps (i) through (iii) discussed above) such that the number of deposited films varies in different regions of the cell. Alternatively, graded can be achieved by tilting the substrate with respect to the spray direction or by fine control of the spray pattern. Fine control can be easily achieved by inkjet printing technology or the use of multiple spray heads.
[0075] In addition to the deposition of ytterbium-doped zirconia crystalline ceramic layers on planar surfaces, such as planar fuel cell surfaces, the present invention is also applicable to deposition on non-planar surfaces. For example, the method of the present invention can be used for the deposition of ytterbium-doped zirconia crystalline ceramic layers for roll or tube-shaped SOCs, wherein a soluble salt precursor solution is deposited, for example, by spraying it onto a rotating tube. In other embodiments, the tube is immersed in the soluble salt precursor solution to cover one or both surfaces of the tube. Thickness control can be achieved by controlling the viscosity characteristics of the solution as well as by rotating the tube during and after immersion. Gradation control of tubular fuel cells can be controlled by changing the depth of immersion during subsequent immersion after the previous layer has dried on the tube. Immersion can also be used on planar fuel cells where masking is used to protect areas of the cell where coating is not required or is undesirable.
[0076] For circular surfaces, such as the surface of a circular fuel cell, a spray pattern suitable for disc coating can be used. To achieve a precise layer thickness of metal oxide crystalline ceramic, the above methodologies of deposition, decomposition, and crystallization can be used. In practice, grading can occur across surfaces such as tubular, cylindrical, or circular surfaces, as in the case of flat surfaces.
[0077] Accordingly, the method of the present invention provides a simple and convenient deposition of a film of ytterbium-doped zirconia crystalline ceramic, particularly a sub-micron layer, without the requirement of high processing temperatures, conventional sintering operations, or expensive high vacuum technology, such as PVD (physical vapor deposition).
[0078] Therefore, this is particularly suitable for the deposition of an intermediate layer on a low or medium temperature metal-supported SOC in cases where conventional sintering becomes more difficult due to the sintering temperature in air or in an air-containing environment limited by the substrate, and where the processing temperature cannot exceed 1100℃.
[0079] Experiments have shown that the method of the present invention is advantageous for forming excellent interfaces between various components because the liquid precursor solution accurately follows the surface topography. This is difficult to achieve by conventional sintering of different materials, particularly when the substrate is already sintered before the deposition of the upper layer, thereby limiting the sintering of the upper layer. In particular, if the interface is located within an SOC electrolyte, a poor interface leads to high ionic resistance as well as mechanical weakness, resulting in increased product failure and a shorter average operating life.
[0080] In a second aspect of the present invention, a layer obtained by a method according to the first aspect of the present invention is provided. The inventors have discovered that an SOC using a layer obtained by a method according to the first aspect of the present invention performs better than a comparable prior art system, or at least comparable to a prior art system using a more complex structure or using more expensive (and / or foreign) materials.
[0081] In a further embodiment of a second aspect of the present invention, a layer for a solid oxide cell comprising crystalline ytterbium-doped zirconia is provided, said layer comprising 12 or fewer films. The inventors have discovered that using ytterbium-doped zirconia allows for the creation of a layer of material having a layered structure (identifiable in the final structure) composed of fewer individual films, while having properties comparable to the prior art. This is highly advantageous because it not only allows the layer to be manufactured more quickly but also reduces the risk of delamination between films and / or other defects occurring at the interface between adjacent films within the layered structure due to the presence of fewer films in the layered structure.
[0082] This is typically the case where the layer contains 10 or fewer films, more typically 8 or fewer films. Often, the layer contains 6 or fewer films, but typically the number of films ranges from 6 to 8, most typically 6.
[0083] As described above in the first aspect of the invention, not all films need to comprise crystalline ytterbium-doped zirconia. However, this is typically the case where all films comprise crystalline ytterbium-doped zirconia.
[0084] In a third aspect of the present invention, a solid oxide cell comprising a layer according to the second aspect of the present invention is provided. Typically, the solid oxide cell is a solid oxide fuel cell. In a further embodiment, a plurality of said cells may be connected to form a fuel cell stack.
[0085] In a fourth aspect of the present invention, a solution for use in the manufacture of an SOC layer is provided, said solution comprising a metal ion salt selected from zirconium salt and ytterbium salt; said zirconium salt is zirconium acetylacetonate; and said solution has a concentration of metal ions of 0.1 M or higher.
[0086] As described above in relation to the first aspect of the present invention, surprisingly, it was discovered that ytterbium improves the solubility of zirconium precursor salts. This allows for the generation of solutions with improved zirconia precursor salt concentrations, thereby increasing the rate at which zirconia can be loaded onto a target substrate.
[0087] Typically, the concentration of metal ions (i.e., the combined concentration of zirconium, ytterbium, and any other metal ions) is in the range of 0.1 M to 0.5 M, more typically 0.1 M to 0.2 M.
[0088] Typically, the solution comprises a solvent as described above. For example, it may be selected from methanol, ethanol, propanol, methoxypropanol, ethyl acetate, acetone, butyl carbitol, or a combination thereof. Among these, it is most common for the solvent to comprise ethanol, which is typically the case where a mixture of ethanol and methoxypropanol is used. Often, the solvent comprises 80% to 95% ethanol and 20% to 5% methoxypropanol; more typically, about 90% ethanol:10% methoxypropanol.
[0089] Additionally, in a fifth aspect of the present invention, a use of the solution according to the fourth aspect of the present invention is provided in the manufacture of an SOC. More typically, said use relates to the manufacture of an SOC layer according to the second aspect of the present invention. Typically, said layer is part of an SOFC. Typically, said use relates to the manufacture of an intermediate layer.
[0090] Now, for the sake of understanding, a preferred embodiment of the present invention will be described in connection with the following drawings and examples. Brief explanation of the drawing
[0091] Figure 1 shows a schematic representation of the method of the present invention. Figure 2 shows a comparison of the ohmic resistance of a solid oxide fuel cell using an 8YbSZ intermediate layer, a solid oxide fuel cell using an 11YbSZ intermediate layer, and a solid oxide fuel cell using a 10Sc1YSZ intermediate layer. Figure 3 shows XRD data of a layer containing 8YbSZ and a layer containing 10Sc1YSZ of the present invention. Figure 4 shows a comparison of the achievable thickness between a layer containing 8YbSZ and a layer containing 10Sc1YSZ of the present invention. Specific details for implementing the invention
[0092] Examples
[0093] Example 1 - Preparation of a Crystalline Ytterbium-Doped Zirconia Layer
[0094] A solution was prepared by dissolving zirconium acetylacetonate and ytterbium(III) nitrate pentahydrate in a solvent mixture of 90 vol% ethanol and 10 vol% methoxypropanol to provide a total molar concentration of 0.14 M metal ions with a zirconium-to-ytterbium ratio of 0.852:0.148. This provided the desired 8 mol% ytterbia in the finished material (crystalline ytterbium-doped zirconia). The salts were dissolved at 50°C, and then the solution was allowed to cool to room temperature.
[0095] A solution was deposited on a half cell of a solid oxide fuel cell of the type described in WO 2016 / 124928 (paragraph
[0052] , Fig. 3 of the literature), consisting of a ferrite stainless steel support and a dense sintered CGO (cerium gadolinium oxide) electrolyte coated thereon.
[0096] Deposition was performed using a spray head on an automated XY stage. The liquid was deposited as discontinuous droplets of a fixed volume, and the deposition frequency and the speed of the XY stage were adjusted so that the liquid droplets covered the entire surface of the portion without overlapping. After deposition, the droplets spread and merged together on the portion to form a uniform liquid film. The total volume of the deposited liquid was adjusted so that the final film was approximately 170 nm thick.
[0097] The resulting liquid film was allowed to dry in still air for 4 minutes, which was long enough for the solvent to evaporate and leave a uniform transparent film of the precursor salt.
[0098] The coated portion of the dried film of ytterbium and zirconium precursor salts was placed over an infrared heater lamp and heated over a 3-minute cycle to reach a temperature in the range of 400°C to 600°C to decompose the precursor salts into an amorphous oxide film, after which it was cooled back to near room temperature. These deposition, drying, and heating steps were repeated two more times to build a layer thickness of approximately 500 nm by three passes.
[0099] Next, the entire half cell was placed in a furnace and heated from room temperature to 800°C in air while increasing the temperature at a rate of 5°C per minute, and a dwell time of 1 hour was allowed to crystallize the amorphous oxide film into an 8YbSZ nanocrystalline film if desired.
[0100] The entire process described above (i.e., deposition, drying, heating, and firing) was repeated one more time to produce a layer of 8YbSZ with a total thickness of approximately 1 μm (i.e., formed by a total of 6 deposition steps).
[0101] Subsequently, a layer of doped ceria was deposited on a layer of 8YbSZ in the same manner as described in WO 2009 / 090419 (page 26, lines 10 to 17 of the document).
[0102] As is known in the art, an air electrode was screen printed on a finished three-layer electrolyte made of perovskite oxide.
[0103] Several additional cells were fabricated using the same process and embedded in a solid oxide fuel cell stack. The electrochemical performance of this stack was compared with a WO 2009 / 090419 system using a 10Sc1YSZ interlayer.
[0104] The internal resistance of the cell was measured as a function of temperature using AC impedance spectroscopy. This allows the internal resistance of the cell to be divided into its constituent parts. The ohmic (series) resistance of the cell includes the resistance to the transport of oxygen ions through the zirconia layer. The ohmic resistance of the cell is exponentially temperature dependent, and plotting the natural logarithm of the ohmic resistance against the reciprocal of temperature produces a straight line (known as the Arrhenius plot).
[0105] As illustrated in FIG. 2, the ohmic resistance of the cell of the present invention using an 8YbSZ interlayer is consistently lower than that of the equivalent 10Sc1YSZ interlayer over the operating temperature range of the low-temperature metal-supported SOC. Specifically, the cell using the 8YbSZ interlayer has a lower ohmic resistance than the cell of the prior art using the 10Sc1YSZ interlayer over a temperature range of 500°C to 610°C. The slope of the line (activation energy) is lower for 8YbSZ, which means that the resistance is less sensitive to temperature and there is a greater performance improvement at lower temperatures. Accordingly, the cell of the present invention has a higher operating voltage and, therefore, a higher power output for any given current compared to the prior art. It has been found that slight changes in the pH of the precursor solution sometimes affect the quality of the deposited film, and that reducing the pH of the solution to below pH 6 by adding acid mitigates this problem.
[0106] Example 2 - Preparation of a Crystalline Ytterbium-Doped Zirconia Layer
[0107] A solution was prepared by dissolving zirconium acetylacetonate and ytterbium(III) nitrate pentahydrate in a solvent mixture of 90 vol% ethanol and 10 vol% methoxypropanol to provide a total molar concentration of 0.08 M metal ions with a zirconium-to-ytterbium ratio of 0.802:0.198. This provided the desired 11 mol% yttervia in the finished material (crystalline ytterbium-doped zirconia). The salts were dissolved at 50°C, and then the solution was allowed to cool to room temperature.
[0108] A solution was deposited on a half cell of the type of solid oxide fuel cell described in WO 2016 / 124928 (paragraph
[0052] , Fig. 3 of the literature), consisting of a ferrite stainless steel support and a layer of dense sintered CGO (cerium gadolinium oxide) electrolyte coated thereon. The purpose of the deposition was to understand the effect of increasing the yttervia dopant concentration from 8 mol% to 11 mol% on conductivity.
[0109] Deposition was performed using a spray head on an automated XY stage. The liquid was deposited as discontinuous droplets of a fixed volume, and the deposition frequency and the speed of the XY stage were adjusted so that the liquid droplets covered the entire surface of the portion without overlapping. After deposition, the droplets spread and merged together on the portion to form a uniform liquid film. The total volume of the deposited liquid was adjusted so that the final film had a thickness of approximately 80 nm.
[0110] The resulting liquid film was dried in still air for 4 minutes, which was long enough for the solvent to evaporate and leave a uniform transparent film of the precursor salt.
[0111] The coated portion of the dried film of ytterbium and zirconium precursor salts was placed over an infrared heater lamp and heated over a 3-minute cycle to reach a temperature in the range of 400°C to 600°C to decompose the precursor salts into an amorphous oxide film, after which it was cooled back to near room temperature. These deposition, drying, and heating steps were repeated 5 more times to build a layer thickness of approximately 500 nm by 6 passes.
[0112] Next, the entire half cell was placed in a furnace and heated from room temperature to 800°C in air while increasing the temperature at a rate of 5°C per minute, and a residence time of 1 hour was allowed to crystallize the amorphous oxide film into a nanocrystalline film of 11YbSZ if desired.
[0113] The entire process described above (i.e., deposition, drying, heating, and firing) was repeated one more time to produce a layer of 11YbSZ with a total thickness of approximately 1 μm (i.e., formed in a total of 12 deposition steps).
[0114] Subsequently, a layer of doped ceria was deposited on a layer of 11YbSZ in the same manner as described in WO 2009 / 090419 (page 26, lines 10 to 17 of the document).
[0115] As is known in the art, an air electrode was screen printed on a finished three-layer electrolyte made of perovskite oxide.
[0116] Several additional cells were fabricated using the same process and embedded in a solid oxide fuel cell stack. The electrochemical performance of this stack was compared with a WO 2009 / 090419 system using a 10Sc1YSZ interlayer.
[0117] The internal resistance of the cell was measured as a function of temperature using AC impedance spectroscopy. This allows the internal resistance of the cell to be divided into its constituent parts. The ohmic (series) resistance of the cell includes the resistance to the transport of oxygen ions through the zirconia layer. The ohmic resistance of the cell is exponentially temperature dependent, and plotting the natural logarithm of the ohmic resistance against the reciprocal of temperature produces a straight line (known as the Arrhenius plot).
[0118] As shown in FIG. 2, the ohmic resistance of the 11YbSZ intermediate layer produced by the method disclosed in the present invention is a function of temperature. It can be seen that the performance of 11YbSZ is intermediate of 8YbSZ and 10Sc1YSZ in both aspects of absolute resistance and activation energy with respect to temperature dependence.
[0119] Example 3 - Preparation of a Crystalline Ytterbium-Doped Zirconia Layer
[0120] A crystalline 8YbSZ zirconia layer was deposited using substantially the same method as described in Example 1, but the solution used was acidified so that the solution concentration was increased to 0.16 M as described below.
[0121] A solution was prepared by dissolving zirconium acetylacetonate and ytterbium(III) nitrate pentahydrate in a solvent mixture of 89.5 vol% ethanol, 10 vol% methoxypropanol, and 0.5 vol% glacial acetic acid to provide a total molar concentration of 0.16 M metal ions with a zirconium-to-ytterbium ratio of 0.852:0.148. This provided the desired 8 mol% ytterbia in the finished material (crystalline ytterbium-doped zirconia). The salts were dissolved at 50°C, and then the solution was allowed to cool to room temperature. The addition of acid further improved the solubility of the zirconium salts in the solution. The pH of the solution was reduced to 4 to 5.
[0122] Subsequently, the solution was deposited substantially as described in Example 1, but to compensate for the higher solution molar concentration, the volume of liquid deposited per portion per pass was slightly reduced by reducing the time the solenoid valve on the spray head was open for each droplet. This ensured that the mass of YbSZ deposited per pass remained similar and that the total desired layer thickness could be achieved in six deposition steps.
[0123] Example 4 - Preparation of a Crystalline Ytterbium-Doped Zirconia Layer
[0124] A crystalline 8YbSZ zirconia layer was deposited using substantially the same method as described in Example 1, but ethyl acetate was used as the main solvent instead of ethanol, so that the solution concentration was increased to 0.16 M without crystallization.
[0125] A solution was prepared by dissolving zirconium acetylacetonate and ytterbium(III) nitrate pentahydrate in a solvent mixture of 90 vol% ethyl acetate and 10 vol% methoxypropanol to provide a total molar concentration of 0.16 M metal ions with a zirconium-to-ytterbium ratio of 0.852:0.148. This provided the desired 8 mol% ytterbia in the finished material (crystalline ytterbium-doped zirconia). The salts were dissolved at 50°C, and then the solution was allowed to cool to room temperature. The addition of ethyl acetate further improved the solubility of the zirconium salt in the solution.
[0126] Subsequently, the solution was deposited substantially as described in Example 1, but to compensate for the higher molar concentration of the solution, the volume of liquid deposited per portion per pass was slightly reduced by decreasing the time the solenoid valve on the spray head was open for each droplet. This ensured that the mass of YbSZ deposited per pass remained similar and that the total desired layer thickness could be achieved in six deposition steps.
[0127] Example 5 - Preparation of a Crystalline Ytterbium-Doped Zirconia Layer
[0128] A crystalline 8YbSZ zirconia layer was deposited using substantially the same method as described in Example 1, but with a small amount of concentrated nitric acid added to the solution to increase the solution concentration to 0.16 M without crystallization.
[0129] A solution was prepared by dissolving zirconium acetylacetonate and ytterbium(III) nitrate pentahydrate in a solvent mixture of 90 vol% ethanol and 10 vol% methoxypropanol to provide a total molar concentration of 0.16 M metal ions with a zirconium-to-ytterbium ratio of 0.852:0.148. This provided the desired 8 mol% ytterbia in the finished material (crystalline ytterbium-doped zirconia). Concentrated nitric acid was added dropwise using a pH probe and under vigorous stirring until the pH of the solution decreased to 3 to 4. The salt was dissolved at 50°C, after which the solution was allowed to cool to room temperature.
[0130] Subsequently, the solution was deposited substantially as described in Example 1, but to compensate for the higher molar concentration of the solution, the volume of liquid deposited per portion per pass was slightly reduced by decreasing the time the solenoid valve on the spray head was open for each droplet. This ensured that the mass of YbSZ deposited per pass remained similar and that the total desired layer thickness could be achieved in six deposition steps.
[0131] Example 6 - Deposited solution concentration
[0132] A solution for intermediate layer deposition was formulated using the same method described above in Example 1. Several solutions were prepared to have various metal ion molar concentrations. The concentrations of these solutions varied from 0.08 M to 0.16 M. Zirconium acetylacetonate was 8YbSZ (ZrO2) 0.92 (Yb2O3) 0.08 With the intention of providing the final oxide composition, ytterbium(III) nitrate pentahydrate was used as a dopant salt in a solvent mixture of 90 volume% ethanol and 10 volume% methoxypropanol. The stability of the solution was investigated and summarized in Table 1 below.
[0133] Stability of the deposition solution Metal ion concentration stability 0.08 M Completely stable for more than 4 weeks. 0.12 M Completely stable for more than 4 weeks. 0.14 M Some fine needle-shaped crystals are formed that remain stable for 3 weeks and are easily redissolved upon stirring and heating. 0.16 M It is immediately unstable and dissolves when heated, but crystals form within 12 hours after cooling back to room temperature.
[0134] In contrast, the solutions prepared according to Examples 3, 4, and 5, respectively, using acetic acid addition, ethyl acetate as the main solvent, or nitric acid addition, were all stable at 0.16 M for more than 4 weeks.
[0135] In contrast, a similar solution using a scandium salt as a dopant, intended to formulate a layer of 10Sc1YSZ (scandium yttrium stabilized zirconia), exhibits a decrease in stability as the metal ion concentration increases above 0.08 M. Acidification and / or the use of ethyl acetate as a solvent allows higher concentrations to be achieved, but the solubility limit is about 0.12 M, which is still significantly lower than that achievable with the use of ytterbium.
[0136] Example 7 - Analysis of the 8YbSZ Interlayer
[0137] FIG. 3 shows the first (111) cubic fluorite crystal plane peaks taken from X-ray diffraction (XRD) measurements using Cu Kα radiation of an 8YbSZ film prepared according to this method and finally calcined at 890°C, and an equivalent prior art 10Sc1YSZ film. The 8YbSZ film exhibits a higher degree of crystallinity, as evidenced by the higher and narrower peaks. The peak positions are also slightly shifted relative to each other, which is consistent with the expected change in cubic crystal lattice parameters between the two materials, and 8YbSZ, Yb 3+ The ion Sc 3+ Because it is slightly larger than an ion, it has a slightly more open lattice. The higher degree of crystallinity of 8YbSZ material means that the crystals within the film are larger, which implies that there are fewer grain boundaries that add resistance to oxygen ion transport, which is potentially beneficial to electrochemical performance. This, in turn, leads to improved cell power output, particularly at lower temperatures (<550°C).
[0138] Example 8 - Analysis of 8YbSZ Interlayer Thickness
[0139] FIG. 4 shows a high-resolution SEM image of a cross-section of an 8YbSZ intermediate layer on a metal-supported SOC deposited as described in Example 1. The 8YbSZ intermediate layer (20) was deposited on top of a dense sintered CGO electrolyte (10) in a total of six passes. Additionally, a thin doped ceria cathode interface layer (30) and an air electrode (40) required for the fabrication of an operating SOC cell can be seen. The interface between the layers, indicated by line (50), is visible in the area of the image and represents six films required to achieve a total intermediate layer thickness of approximately 1 μm, indicated by the scale bar at the bottom of the image. In contrast, the prior art process requires 12 films to achieve the same thickness.
[0140] Example 9 - Effect of Dopant %Yb Level on Solution Solubility
[0141] Since zirconium cations are a limiting factor in the solubility of the intermediate layer precursor solution, as the level of z, i.e., the % of the Yb cation dopant, decreases, the amount of zirconium cations increases correspondingly. Thus, the 0.14 M solution as described in Example 1, having a Yb dopant level of 12 mol%, is excellently soluble and provides a solution, whereas a lower dopant level of 6 mol% at the same molar concentration had lower overall solubility, causing slight recrystallization.
Claims
Claim 1 A method for producing a crystalline ytterbium-doped zirconia layer on a substrate, the method comprising: (i) depositing a solution containing a precursor metal salt of ytterbium-doped zirconia onto a surface of the substrate, wherein the surface is a metal or ceramic surface; (ii) drying the solution to form a film of the precursor metal salt on the surface; (iii) heating the film of the precursor metal salt to decompose it to form ytterbium-doped zirconia; (iv) optionally repeating steps (i) to (iii); and (v) calcining the film(s) to form the crystalline ytterbium-doped zirconia layer, wherein the pH of the solution is in the range of 2 to 6. Claim 2 A method according to claim 1, wherein the substrate comprises a dense solid oxide electrolyte for a solid oxide cell, and the crystalline ytterbium-doped zirconia layer is formed on the substrate. Claim 3 A method according to claim 1, wherein the layer comprises crystalline ytterbium-doped zirconia having a cubic crystal structure. Claim 4 A method according to claim 1, wherein the above-mentioned material in step (i) has a temperature in the range of 10°C to 100°C. Claim 5 A method according to claim 1, wherein the temperature of step (iii) is in the range of 200℃ to 600℃. Claim 6 A method according to claim 1, wherein the precursor metal salt comprises a zirconium salt and an ytterbium salt, and the zirconium salt is zirconium acetylacetonate. Claim 7 A method according to claim 1, wherein the solution further comprises an acid selected from acetic acid, citric acid, nitric acid, or a combination thereof (typically, a weak acid). Claim 8 The method of claim 1, wherein the temperature in step (v) is in the range of 500°C to 1100°C, typically 700°C to 1000°C. Claim 9 A method according to claim 1, wherein step (iii) further comprises the step of cooling the layer to a temperature of less than 150°C. Claim 10 In claim 1, the method wherein the ytterbium-doped zirconia has the following chemical formula: ([Yb x M 1-x ]2O3) z (ZrO2) 1-z In the above formula, M is a metal dopant ion; z is in the range of 0.03 to 0.13; and x is in the range of 0.05 to 1. Claim 11 A method according to claim 1, comprising an additional step in which steps (i) to (v) are repeated at least once, wherein, in the additional step, the substrate comprises the crystalline ytterbium-doped zirconia layer previously prepared in step (v). Claim 12 A method according to claim 1, wherein the layer has a thickness in the range of 0.9 μm to 1.2 μm. Claim 13 A layer obtained by the method according to paragraph 1. Claim 14 A layer for a solid oxide cell obtained by the method according to claim 1, wherein the layer comprises 6 to 8 films, each of which comprises crystalline ytterbium-doped zirconia. Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete Claim 20 delete Claim 21 delete Claim 22 delete Claim 23 delete Claim 24 delete Claim 25 delete Claim 26 delete Claim 27 delete Claim 28 delete Claim 29 delete Claim 30 delete Claim 31 delete Claim 32 delete
Citation Information
Patent Citations
Air electrode material for solid oxide fuel cell
JP2012164672A
Method for deposition of ceramic films
WO2009090419A2
